Oltre la sbarra . Beyond the Barrier - Leopardi, Marco (Blu Film - Terra, 2006)
Verzio FF Submission The memory of the Chernobyl disaster has more or less faded. However, in Belarus the permanent road blocks that deny entry to the most highly radioactive areas are the proof of an emergency which has never faded. We follow Massimo Bonfatti and his dedicated volunteers who started the project “Humus” in order to do something about the effects of the contamination. They provide information to villagers about the radiation and teach them how to protect themselves from the radioactivity.